Cystatin C Use for CKD Detection in the Veterans Health Administration System: A Qualitative Study of Barriers and Facilitators - Julio A. Lamprea-Montealegre; Abigail Shapiro; Natalie A.B. Bontrager; Dena E. Rifkin; Simerjot K. Jassal; Lucile Parker Gregg; Sankar D. Navaneethan; Krista Navarra; Michael G. Shlipak; Michelle M. Estrella; Virginia Wang (Kidney Medicine, 2024)
Rationale & Objective: The measurement of cystatin C has been recommended to enhance chronic kidney disease (CKD) detection and risk stratification in clinical practice. This study gathered insights into the perceptions and experiences of clinical staff regarding the use of cystatin C in CKD detection within the Veterans Health Administration (VHA) system. Study Design: A qualitative approach was employed to explore barriers and facilitators of clinical staff regarding the use of cystatin C in CKD detection within the VHA system. The Organizational Theory of Implementation Effectiveness informed the development of a semistructured interview guide. Setting & Participants: Health care providers, nurses, and clinical pharmacists from the VHA systems in San Francisco, San Diego, and Houston were interviewed between October 2021 and May 2022. Exposures: Participants' experiences with cystatin C testing. Outcomes: Perceived barriers and facilitators to cystatin C testing. Analytical Approach: Participant responses from individual interviews were analyzed by a multidisciplinary team using rapid qualitative analysis methods. Results: Fourteen in-depth interviews were conducted across the 3 VHA systems. Ten of 11 providers worked in primary care. Five key barriers to using cystatin C for CKD detection were identified. These included lack of patient awareness of CKD testing, lack of provider awareness about cystatin C, knowledge barriers about cystatin C testing, unclear roles and ownership of CKD detection, and lack of clinic support to enhance CKD detection. Suggested interventions to overcome these barriers included educational and training programs, improved clinic workflows, and electronic health record aids to support CKD detection and use of cystatin C. Limitations: The results may not be generalizable to other health care systems outside the VHA. Conclusions: The findings indicate a need for targeted interventions such as educational and training programs, improved clinical workflows, and electronic health record aids to address barriers limiting the use of cystatin C in clinical practice for enhanced CKD detection. Plain-Language Summary: This study assessed how clinical staff at the Veterans Health Administration (VHA) feel about using a test called cystatin C to help detect chronic kidney disease (CKD) earlier and more accurately. The research team spoke to healthcare providers, nurses, and clinical pharmacists in San Francisco, San Diego, and Houston between October 2021 and May 2022. We conducted 14 detailed interviews to understand the challenges and opportunities in using cystatin C for CKD detection. We found that participants often lacked awareness of CKD and the benefits of testing with cystatin C. There were also gaps in knowledge about how to use the test effectively, confusion over who should be responsible for CKD detection, and a need for better support within clinics to use cystatin C. To address these issues, there should be more educational programs for both staff and patients, improvements in clinic processes, and enhancements to electronic health records to better support CKD detection using cystatin C. However, the results from this study might not apply to other healthcare systems outside the VHA.